Phenotypic and molecular characterization of K64 putative hypervirulent carbapenem-resistant Klebsiella pneumoniae - Chunhong Shao; Jian Bao; Xinying Wang; Yan Jin; Ren Ren; Wei Wang; Meijie Jiang (PLoS ONE, 2026)
Objectives Although K64-type carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-hvKp) has been reported, its molecular characteristics remain unclear. This study aimed to characterize the phenotypic and molecular features of K64 putative hypervirulent CR- K. pneumoniae (phvKp).. Methods Two K64 putative hypervirulent CR- K. pneumoniae isolates were recovered from a patient in the emergency intensive care unit of a Chinese teaching hospital. Antimicrobial susceptibility testing was performed using broth microdilution method. Multilocus sequence typing (MLST) was used for molecular typing. Virulence was assessed using a mouse infection model, and whole-genome sequencing was performed to analyze resistance and virulence genes. Results Both isolates were resistant to aztreonam, cephalosporins, carbapenems, quinolones, and aminoglycosides, but susceptible to trimethoprim/sulfamethoxazole, colistin, tigecycline, and ceftazidime/avibactam. MLST identified both isolates as ST11. The mouse infection model showed elevated virulence of two clinical isolates, which was significantly higher than that of the classical non-hypervirulent reference strain ATCC 13883. Genomic analysis identified 133 virulence- and pathogen-associated genes, including those involved in fimbriae synthesis, iron acquisition, and enterobactin production. Both isolates harbored the rmpA gene, but string tests were negative. Sequence alignment revealed >80% similarity among 13 rmpA-harboring IncHI1B plasmids. Conclusions K64 ST11-type phvKp has emerged in China, exhibiting multidrug resistance and putative hypervirulence characteristics. The increase in virulence of K.pneumoniae involves multiple factors, and these factors act independently or the synergistic effect leads to elevated virulence potential.